Analysis of Biology Learning Planning on Plant Tissue Course in the Independent Learning Activity Unit (UKBM) based on Scientific Approach Class XI MIPA 5 at MAN Sumenep - Romdaniyah, Suci; Nasution, Nanda Eska Anugrah; Rizka, Chairany (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
This article presents a study conducted at MAN Sumenep, the only State Madrasah Aliyah in Sumenep Regency that has implemented the Semester Credit System (SKS) and the Usage of Scientific Approach (UKBM) program. The qualitative research method was used, and data were collected through observation, interviews, and documentation. The findings reveal that MAN Sumenep follows a well-structured planning process for biology learning, including the preparation of syllabus, annual and semester programs, effective week plans, and lesson plans integrated with UKBM content. Special training sessions are conducted for teachers to develop UKBM, and resource persons are invited from the Ministry of Religion's Pusdiklat. The evaluation and review of UKBM are carried out regularly, and revisions are made if necessary. Overall, the article highlights the effective implementation of UKBM in MAN Sumenep, which can serve as a valuable model for other schools.